Abstract 6 Projected Impact of Omidubicel on Racial and Ethnic Disparities in Allogeneic Hematopoietic Cell Transplant Access and Outcomes for Patients with Hematologic Malignancies in the U.S. (6th September 2022) - Gergis, Usama; Khera, Nandita; Edwards, Marie Louise; Song, Yan; Sun, Rochelle; Simantov, Ronit; Sivaraman, Smitha; Manghani, Rocio; Signorovitch, James
Abstract: Introduction: Patients with hematologic malignancies (HM) who are eligible for allogeneic hematopoietic cell transplant (allo-HCT) often lack an HLA-matched related donor (MRD) and rely on unrelated donors for a matched or mismatched unrelated donor (MUD or MMUD) or on umbilical cord blood (UCB). It is well known that racial minorities are underrepresented in donor registries. Objective: Omidubicel, an advanced cell therapy for allo-HCT, demonstrated superior hematopoietic recovery and clinical outcomes compared with standard UCB (NCT02730299). We hypothesized the impact of omidubicel access on racial and ethnic health disparities in a projection model. Methods: A model was developed to project allo-HCT access and clinical outcomes in a hypothetical population of 10, 000 allo-HCT-eligible US patients with HM lacking an HLA-MRD. Outcomes associated with omidubicel, MUD, MMUD, haploidentical or UCB HCT, or no transplant were assessed by race/ethnic group. Model inputs, including clinical outcomes for each HCT type, were drawn from clinical trials, public CIBMTR and US Department of Health and Human Services data, and published studies. Increasing omidubicel use was modeled, with proportional reductions in other allo-HCT types or no transplant. Results: In a modeled population of 10, 000 patients, 5, 956 (60%) received allo-HCT utilizing current donor sources (MUD, MMUD, haploidentical, UCB) with no omidubicel (status quo). While 80% of white patients underwent allo-HCT, only 40% of Hispanic, 32% of Asian, and 22% of Black patients underwent allo-HCT. Mean time from selecting graft to HCT was 11.5 weeks. Including those not transplanted, 1-year OS was 62% overall, ranging from 56% (Black) to 65% (White). Modeled increases in omidubicel use in eligible patients were associated with higher proportions of patients undergoing allo-HCT, decreased time to HCT, and increased 1-year OS. Improvements were greatest among racial minorities. Assuming 20% omidubicel use, the proportion of patients receiving allo-HCT increased by 71% in Black, 43% in Asian, 30% in Hispanic, and 5% in White patients. Modeled time to allo-HCT improved as well. Discussion: Access to omidubicel is projected to decrease time to allo-HCT, improve outcomes overall, with greatest improvements among racial and ethnic groups underserved by the status quo, thus helping to reduce racial disparities and improving health equity in allo-HCT.